SIX1 is upregulated in gastric cancer and regulates proliferation and invasion by targeting the ERK pathway and promoting epithelial‐mesenchymal transition. (31st October 2018) - Xie, Ying; Jin, Peng; Sun, Xuren; Jiao, Taiwei; Zhang, Yining; Li, Yue; Sun, Mingjun
Abstract : Sine oculis homeobox homologue 1 (SIX1) is a Six class homeobox gene conserved throughout many species. It has been reported to act as an oncogene and is overexpressed in many cancers. However, the function and regulatory mechanism of SIX1 in gastric cancer (GC) remains unclear. In our study, we detected protein levels of SIX1 via immunohistochemistry (IHC) and its proliferation and invasion effects via CCK8 and transwell assays. Additionally, expression of cyclin D1, MMP2, p‐ERK, and EMT‐related proteins was measured by western blotting. We found that SIX1 had significantly higher expression in GC tissues and that it could promote GC cell proliferation and invasion. Also, overexpression of SIX1 increased the expression of cyclin D1, MMP2, p‐ERK, and EMT‐related proteins, which could all be inhibited by knocking down SIX1. In conclusion, SIX1 is upregulated in GC tissues. It can promote GC cell proliferation by targeting cyclin D1, invasion via ERK signalling, and EMT pathways by targeting MMP2 and E‐cadherin. Significance of the study: Our study showed that SIX1 was upregulated in GC tissues, and promoted GC cell proliferation by targeting cyclin D1, invasion via ERK signalling, and EMT pathways by targeting MMP2 and E‐cadherin. These results suggested the potential regulatory mechanism of SIX1 in proliferation and invasion of gastric cancer.